Effect of Archival-based Content on Instagram Engagement: A Study on @arsipugm - Thoriq Tri Prabowo; Nora Saiva Jannana; Siwi Anjarwati (Arsip Universitas Gadjah Mada, 2023)
This studyaims to examine the effect of archival-based content types on Instagram engagement in an archival institution in Indonesia. This is quantitative study. Data were obtained from the Instagram log content included like and comment number, within February 2023 to July 2023. There were 63 contents in that period. The contents were categorized into five categories: (A) greeting to followers; (B) archival material; (C) daily news; (D) promoting the services; and (E) archival knowledge. One-way analysis of variance (ANOVA) was employed to analyze the data. The results revealed that there was a significant difference on “likes” mean score among the content types. On the other hand, content types had no significant effect on “comments” mean score. Implementation of principles of social media optimization is suggested to enhance the Instagram engagement. This study offers an intentional approach for archival institutions to enhance their engagement in social media.